Stress Distribution and Displacement of Craniofacial Structures Following Force Application in Treatment of an Operated Bilateral Facial Cleft - Kunal V. Shet; K. Nillan Shetty; Rohan Rai; Anurag D. Mahale (Galenos Yayinevi, 2014)
Objective:The purpose of this study was to analyze the stress distribution and displacement patterns within the craniofacial structures following application of transverse and anteriorly directed forces by means of rapid maxillary expansion and reverse pull headgear, respectively, using a finite element method in a patient with bilateral cleft.Materials and Method:A finite element model was used to determine stress distribution and displacement of various craniofacial structures following application of transverse and anteriorly directed forces.Results:Maximum forward displacement was 8.07 mm at the node corresponding to the incisal edge of the upper central incisor followed by 7.95 mm at the prosthion. Maximum positive displacement lateral displacement was 3.24 mm at the node representing the premolars. The lateral and medial pterygoid plates showed maximum superior movement of about 0.95 mm and 0.79 mm, respectively. In the dentoalveolar region, the stresses were highest in the apical region of the canine. In the maxilla, point A and ANS demonstrated higher stress values compared with previous studies; both inferior and superior surfaces demonstrated high stresses in the range of 10.11 to 10.20 kg/mm2.Conclusion:Although expansion can be achieved in adolescents, displacements are noted more in the structures located anteriorly and along the midline while the posterior and lateral structures demonstrate minimal displacement but high stresses. Rapid maxillary expansion must be used judiciously in adolescents because of its far-reaching effects involving heavy stresses noted at the sphenoid bone, zygomatic bone, nasal bone, and their adjacent sutures.